Application of The Model of Risk Classes (MRC model) In Covid Time - Katarzyna CHŁAPEK (Communications of International Proceedings, 2020)
The phenomenon of economic risk is the subject of many scientific considerations, and measuring it has been identified as a challenge. In addition, the current situation of the COVID-19 pandemic has a significant impact on business security around the world.  The aim of the article is to draw attention to the possibility of measuring economic risk using discriminatory analysis tools, in the form of a model of risk classes. The advantage of the model is the availability of data from a financial statement. The study used official financial data of companies listed on the Warsaw Stock Exchange (WSE) and information collected from the websites of the entities subject to the study. The study shows that it is possible to use the proposed model in the economic risk analysis of units. This article recognises the need for future studies on how to adapt the model to current conditions, especially in the areas of non-financial data, in order to include them in the model of risk classes. The results of the study can be useful to both scientists and practitioners interested in economic risk assessment in economic entities.
Keywords: measurement of the risk; model of classes of the risk; discriminatory analysis; COVID